Assessment of the quality of IMCI implementation in four districts in Zimababwe - Habimana, Phanuel (My University, 2010)
The Integrated Management of Childhood Illness (IMCI) strategy was introduced in Zimbabwe in 1996 to integrate vertical child health care programmes. It has since expanded to cover over 300 first level health facilities out of 897 in 23 districts out of a total of 59 districts in the country. This survey was conducted to measure the quality of care delivered to sick children aged 2 months up to 5 years at first level health facilities implementing IMCI. The management of sick children was observed for 226 children aged 2 months up to 5 years who were brought to primary level health facilities. 226 interviews with child caretakers were conducted, all children included in the survey were re-examined by an experienced IMCI practitioner to ascertain the classification (diagnosis) of child’s illness and the appropriate treatment needed. Finally facilities, services and supplies were assessed in the 35 facilities visited. Seventy one percent of cases were children under 2 years old. The majority of caretakers (88%) were mothers of the sick children. All children were systematically checked for the four main symptoms, 80% of children were checked for general danger signs. About 70% of cases classified as having pneumonia received correct treatment for pneumonia. Almost 50% of cases observed received correct treatment for malaria. Half of the children observed (50%) received their 1st dose at the facility. Just less than half (48%) of the children who needed vaccines left the health facilities with all the needed vaccines. Eighty five percent of caretakers were advised on drug treatment. As a result of the advice received, almost two third (65%) of the caretakers who had been prescribed an antibiotic/antimalarial were able to correctly describe how to give the antibiotic to the iv child. The large majority of caretakers (78%) were satisfied with the health services provided. Over half (54%) of facilities visited had at least 60% of health workers trained in IMCI; 88% of children were managed by health workers who had been trained in IMCI. Drugs were available with the exception with oral rehydration salts (ORS) or sugar salt solution (SSS). Most facilities had supplies and equipment for vaccination, and most had other basic supplies and materials; IMCI chart booklets were found in 91% of facilities. Health facilities which received at least one supervisory visit that included observation of -case management in the last 6 months was only 11% indicating that supervision is not carried out on a regular basis. The management of sick children seen by providers trained in IMCI followed a systematic approach in most cases but there is room for further improvement. Drugs were used rationally. Key supportive elements of the health system were in place in the facilities visited with the exception of regular supervision. However only 38% needing urgent referral were identified and prescribed urgent referral. Weaknesses were also observed in the management of diarrhea, fever and in counseling the caretaker. Only 15% of caretakers were given or shown the mothers card as a job aid and only 23% of caretakers were told on when to return immediately. The IMCI strategy has the potential to act as a powerful channel to improve the quality of services. As the survey was unable to determine reasons for poor performance observed, further research is required to investigate the factors leading to poor health worker performance.
MPH, Faculty of Haelth Sciences, University of the Witwatersrand, 2009
Keywords: Integrated Management of Childhood Illness; child health care; Zimbabwe